PENGEMBANGAN ALAT DESTILASI SEDERHANA UNTUK PENGUATAN KAPASITAS PRODUKSI ASAP CAIR HERBAL ANTI DIABETES BERBASIS ARDUINO DENGAN KONTROL SUHU OTOMATIS DI CV. MOGA PERMATA PERKASA - Gimelliya Saragih; Fauzatu arabica Yatasya Hasibuan; Abdul Aziz Rahmansyah; Yenny Sitanggang; Dejoi Situngkir; Said Hanief; Dimas Frananta; Evita Wahyu; Vivi Purwandari (Journal of Golden Generation Abdimas, 2025)
The limitations of conventional distillation technology hinder micro, small, and medium enterprises (MSMEs) from producing herbal products with consistent quality. This study aims to develop an Arduino-based distillation system equipped with automatic temperature control to improve the production capacity and quality of herbal liquid smoke at CV Moga Permata Perkasa. The research methods include system design and fabrication, functional testing, operator training, and performance evaluation. The results demonstrate a 35% increase in production capacity and stable temperature control within a ±2°C range during the distillation process. These findings indicate that the developed system effectively enhances production efficiency and product consistency. Furthermore, the proposed technology is affordable, easy to operate, and has strong potential for implementation and replication among similar MSMEs.